Concrete and the barriers to innovation in UK housebuilding - Siebert, Michael (2019)
It is widely accepted that our housing industry is in crisis. Like most crises this has not happened overnight but comes after many decades during which little progress has been made from within and the numerous government white papers calling for change have gone unheeded. The proposition put forward in this thesis is that too much attention is being given to the benefits to be gained from innovation within the industry, at the expense of understanding the barriers that are preventing those innovations from being adopted, or possibly even from being considered. That lack of understanding represents a gap in our knowledge that could potentially mean the difference between our housing industry continuing on its current trajectory and it transitioning to a more sustainable path which can provide us with more, better quality, truly affordable housing. The initial aim of this research was to discover what those barriers were, by looking at the industry from all possible perspectives and capturing any influencing factors that might have been previously overlooked. The methods used to achieve this were a series of industry interviews across all sectors, together with on–line questionnaires and an analysis of government produced recommendations. By asking each sector in turn about their knowledge and perceptions of how the other sectors operated, a picture emerged of an adversarial, fragmented industry that was failing to understand the motivations and drivers of those it must collaborate with to bring about change. From this stemmed the realisation that, more than anything else, it was a process that was needed to help the industry deal with the many complex, interrelated problems it faces, that not only have to be recognised as such, but also assessed for their comparative impact on the decisions being made. Through a series of twenty case studies, a set of decision making tools were therefore developed, tested and validated against known issues spanning the whole remit of innovation within housing, using the concrete industry as the vehicle for this process throughout. There were many findings taken from this interrogation of the barriers to innovation, with relevance to the industry as a whole both from the perspective of those promoting and those wanting to adopt innovative solutions. By questioning what laid behind each barrier in turn, a model was constructed that showed a hierarchy of causes and consequences and exposed the true root causes that this process suggests must be dealt with. Whilst the practical lessons learnt from this exercise were strategically important, the more urgent message that should be taken from this is the need for a more holistic decision making process that can lay out the options available to the housing industry with greater clarity and allow decision makers to make their own, more informed choices.